METAPHOR IN NEWSPAPERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Whether metaphor identification in newspapers is straightforward or may pose difficulties has not been reported before. The Pragglejaz Group (2007) demonstrated the MIP procedure by applying it to a sentence from a news article, which hints that the procedure is particularly transparent for the news register. In the original Pragglejaz article, however, the procedure was developed by analyzing just a handful of sentences. One might expect application of the method to a large amount of data, as carried out in my project, to reveal cases that fall beyond the protocol, and, indeed, its application to larger samples of text has led to some adjustments.